Theoretical and experimental investigation of Lamb waves excited by partially debonded rectangular piezoelectric transducers. (16th March 2020) - Shpak, A N; Mueller, I; Golub, M V; Fritzen, C P
Abstract: The paper proposes a new hybrid approach technique to simulate acousto-ultrasonic wave excitation and propagation due to operation of the partially debonded piezoelectric transducer attached to a plate-like structure. The semi-analytical boundary integral equation method is applied to calculate guided waves propagation in the unbounded structures and to separate different guided waves in the piezo-induced wave-fields. The obtained model is verified experimentally using the scanning laser Doppler vibrometry. Eigenfrequencies are calculated and analysed for various sizes of the transducer and for different bonding conditions between the transducer and the waveguide. The impact of the transducer's height, size and debonding area on symmetric and antisymmetric Lamb waves excitation is analysed. The paper demonstrates that one-sided debonding of the transducer exerts intense influence on the distribution of the wave energy among the excited Lamb wave modes, while center debonding has a sizable impact only at relatively high frequencies.